Seismic cracking and instability of concrete dams: Smeared crack approach. (June 2015) - Hariri-Ardebili, M.A.; Seyed-Kolbadi, S.M.
Highlights: An advanced rotating smeared crack model is developed. Rotating smeared crack is compared with fixed single crack model. Failure modes of three concrete dam types (gravity, buttress and arch) are studied. Dynamic foundation-dam-reservoir interaction is taken into account. Instability of the numerical model is investigated using the through crack theory. Abstract: Modeling the material behavior and estimation of the cracking capacity of concrete dams under the dynamic loading is important for safety operation purposes. In the present paper, an improved 3D co-axial rotating smeared crack model is used with the ability of updating the variable shear transfer coefficient. The model is implemented in the finite element code to assess the seismic cracking of three types of concrete dams, i.e. gravity, buttress, and arch dams. Results of the crack profiles confirm importance of the shear transfer coefficient in dynamic analysis of large concrete structures. It is found that the proposed model lead to less diffused cracks in concrete dams and can reasonably matches with the results obtained from experimental tests.